Konsep Maslahat di Tengah Budaya Hukum Indonesia - Firdaus, Robitul (Fakultas Syariah IAIN Purwokerto, 2011)
Maslahat is one of the approaches which is usually used by Indonesian moslem scholars to solve gap problems between Islam and world development. It also causes many contradictions amongst them, however, because of its flexibility. some scholars use maslahat without clear boundaries and apply it as a free method. The writer tries to give a solution about this problem, especially when maslahat faces the culture of Indonesian law system. Maslahat has universal characteristic. Therefore, it should be acceptable and applicable in universal ways. In Indonesian context, maslahat must be formalized and institutionalized in Indonesian law system if it will be applied as universal value in the middle of Indonesian society. Consequently, if there is a conflict amongst several applications from maslahat, Indonesian law system could have the right to determine the truth.